"Soetwyn": Visuality, Cultural Tourism, Desire Paths and the ≠Khomani. Issue 1 (1st January 2017) - Mboti, Nyasha
Abstract : Witdraai is home to a few hundred ≠Khomani who resettled there after the successful land claim of 1999. In all, the first phase of their claim granted them ownership of six farms totaling about 40, 000 hectares of land. Before this restitution, the Bushmen had been an "Other-diaspora" dispersed by the forces of apartheid and colonialism. Being a small settlement in the vast Kalahari in Northern Cape Province, close to the Botswana border, Witdraai is rarely a cartographic highlight where the province's main towns, cities and localities are concerned. For over a decade the ≠Khomani have been involved in trying to find solutions to the problem of appropriate development of the six farms for sustainable communal benefit. Alcohol abuse among many of the residents, however, seems to be complicating the search for lasting solutions. This article uses visual stills, collected during the 2011 trip to the Kalahari by University of KwaZulu–Natal researchers from the Centre for Communication, Media and Society (CCMS), to investigate alcohol use/abuse amongst some of the people living at or near Witdraai. The article applies "cultural mapping" of a different sort, focusing selectively on visual traces of the corporeal existence of "alcohol" in the sand-dune landscape of Witdraai against a backdrop of commercial tourist branding of the landscape.